2016
DOI: 10.2967/jnumed.115.165498
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Myocardial Blood Flow and Flow Reserve Assessed by Gated SPECT with Cadmium–Zinc–Telluride Detectors Using 99mTc-Tetrofosmin: Head-to-Head Comparison with 13N-Ammonia PET

Abstract: Recent advances in SPECT technology including cadmium-zinctelluride (CZT) semiconductor detector material may pave the way for absolute myocardial blood flow (MBF) measurements by SPECT. The aim of the present study was to compare K 1 uptake rate constants as surrogates of absolute MBF and myocardial flow reserve index (MFRi) in humans as assessed with a CZT SPECT camera versus PET. Methods: Absolute MBF was assessed in 28 consecutive patients undergoing adenosine stress-rest myocardial perfusion imaging (MPI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 31 publications
(34 reference statements)
3
53
0
4
Order By: Relevance
“…Data are acquired in a list mode enabling dynamic SPECT radiotracer myocardial blood flow imaging in a tomographic mode. 16,17 Indirect photon detection with solid-state photodiodes (Cardius, Digirad, Suwanee, GA). Another approach is to couple pixelated scintillation crystals to solid-state photodiodes instead of PMTs.…”
Section: System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are acquired in a list mode enabling dynamic SPECT radiotracer myocardial blood flow imaging in a tomographic mode. 16,17 Indirect photon detection with solid-state photodiodes (Cardius, Digirad, Suwanee, GA). Another approach is to couple pixelated scintillation crystals to solid-state photodiodes instead of PMTs.…”
Section: System Designmentioning
confidence: 99%
“…The feasibility of this approach has been demonstrated in a large animal model, 155 but at this time SPECT MBF and MFR measurements in humans are very new. While the results have been very encouraging, investigations with both conventional rotating systems 156,157 and non-rotating cardiac cameras 15,17,158,159 have been limited to single-center feasibility studies. While the benefits of PET-based MBF/MFR are clear, [160][161][162][163] no published study has currently evaluated the incremental diagnostic and prognostic value of SPECT MBF and MFR measurements; more investigations are ongoing in this area.…”
Section: Spect Myocardial Blood Flow Quantitation Introductionmentioning
confidence: 99%
“…Figure 1 demonstrates representative time-activity curves and k 1 polar maps obtained from attenuation and scatter-corrected images at rest and during dipyridamole stress with LAD occlusion. In a human study, 19 MBF and MFR obtained by CZT-SPECT with CT attenuation correction were compared to those obtained by N-13 ammonia PET. While resting MBF was similar, hyperemic MBF was lower for CZT compared to PET, yielding significantly lower MFR for CZT-SPECT compared to PET.…”
Section: Dynamic Spect Imagingmentioning
confidence: 99%
“…8 Additional critical weakness of measuring MBF using Tc-99m-labeled tracers is its low extraction fraction. By the first human study comparing MBF data from dynamic CZT acquisition with data from PET Nkoulou et al 9 showed that median MBF at rest was comparable between CZT and PET, whereas it was significantly lower at stress in CZT than PET. This resulted in median myocardial flow reserve values of 1.32 by CZT, which is very low as compared to the usual cutoff value of 2.0 by many PET-based studies.…”
Section: Measurement Of Mbf and Cfrmentioning
confidence: 99%